PENGUJIAN SUMBER PANAS BIOGAS SEBAGAI ALTERNATIF PENGGANTI GAS LPG PADA INPUT GENERATOR MESIN PENDINGIN ABSORPSI DIFUSI XD-70 (AMMONIA-AIR) - VIRA DHATUL FAUZIAH (2020)
Currently the refrigeration system in Indonesia has improved rapidly. Due to the increased consumption of cooling energy in buildings and the need to reduce CO2 emissions to the environment, the interest in using renewable energy sources appears stronger than in previous years. Biogas alternative energy is renewable energy which can be used as a substitute for LPG fuel for input absorption diffusion absorption coolers. In this test, the absorption cooling system used is the ammonia-water absorbent fluid pair. This refrigeration system does not require electrical energy and only uses thermal energy to operate. The heat source used to operate this system is the heat obtained from LPG gas and biogas. The study was conducted by varying the cooling load in the diffusion absorption cooling engine cabin. The study used 3 kg LPG gas and 4 m3 of biogas capacity. The results obtained from the study are the optimum mref is 1.41 gr / s, the optimum Qgen is 1541.8 watts, the optimum Qevap is 3436.9 watts and the optimum COP is 0.4537. The higher the cooling load, the evaporator cooling capacity (Qevap) and COP value will be higher.